STRATEGIC MARKETING – DIRECTION OF THE TOURISM DEVELOPMENT IN THE GLOBALIZATION PROCESS - Karolina ILIESKA (Revista de Turism: Studii si Cercetari in Turism, 2006)
One of the basic characteristics of modern enterprises business is a constant change of the role and significance of particular activities in the value chains. That increases the need of some additional information that are mainly collected, created and given by marketing. A share of the cost of marketing information increases in the total cost structure, so information management becomes a core resource of the competitive advantage. The marketing information is the glue that holds together the structure of all business and, consequently, the stakeholders in the profit chains. It implies certain new approaches in the marketing theory and practice. The intention of the author is to point out some key changes that are the challenges of marketing in the global environment. They are the threats but also the strengths for marketing development of economies in transition.